Effect of gender on computerized electrocardiogram measurements in college athletes - Mandic, S.; Fonda, H.; Dewey, F.; van Le, V.; Stein, R.; Wheeler, M.; Ashley, E. A.; Myers, J.; Froelicher, V. F. (The Physician and Sportsmedicine, 2010)
Abstract: Background Broad criteria for classifying an electrocardiogram (ECG) as abnormal and requiring additional testing prior to participating in competitive athletics have been recommended for the preparticipation examination (PPE) of athletes. Because these criteria have not considered gender differences, we examined the effect of gender on the computerized ECG measurements obtained on Stanford student athletes. Currently available computer programs require a basis for "normal" in athletes of both genders to provide reliable interpretation. Methods During the 2007 PPE, computerized ECGs were recorded and analyzed on 658 athletes (54% male; mean age, 19 ± 1 years) representing 22 sports. Electrocardiogram measurements included intervals and durations in all 12 leads to calculate 12-lead voltage sums, QRS amplitude and QRS area, spatial vector length (SVL), and the sum of the R wave in V5 and S wave in V2 (RSsum). Results By computer analysis, male athletes had significantly greater QRS duration, PR interval, Q-wave duration, J-point amplitude, and T-wave amplitude, and shorter QTc interval compared with female athletes (all P < 0.05). All ECG indicators of left ventricular electrical activity were significantly greater in males. Although gender was consistently associated with indices of atrial and ventricular electrical activity in multivariable analysis, ECG measurements correlated poorly with body dimensions. Conclusion Significant gender differences exist in ECG measurements of college athletes that are not explained by differences in body size. Our tables of "normal" computerized gender-specific measurements can facilitate the development of automated ECG interpretation for screening young athletes.